2022
DOI: 10.1515/jpem-2022-0136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 pandemic on presentation and referral patterns of newly diagnosed children with type 1 diabetes in a developing country

Abstract: Background The global spread of coronavirus disease 2019 (COVID-19), had a great impact on patients worldwide, including those with chronic diseases. We aim to study the effect of COVID-19 pandemic on presentation patterns of patients with type 1 diabetes (T1D) in Jordan, as an example a developing country with limited resources. Methods Medical charts were reviewed for patients presented with new-onset T1D to Jordan Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In this systematic review and meta-analysis, in 17 studies including 38 149 children and adolescents with newly diagnosed type 1 diabetes, 13, 23, 24, 27, 31, 32, 38, 39, 49-51, 53, 55, 58-60, 63 we found that the incidence rate of type 1 diabetes was 1.14 times higher in the first year and 1.27 times higher in the second year after the onset of the COVID-19 pandemic compared with before the pandemic. In 15 studies including a total of 4324 children and adolescents with DKA, 27,29,36,37,[40][41][42][44][45][46][47]49,50,54,65 we also found that the incidence rate of DKA at diagnosis was 1.26 times higher in the first year after the onset of the COVID-19 pandemic compared with before the pandemic. The magnitude of increase in the incidence rate of type 1 diabetes that we observed after the onset of the pandemic was greater than the expected 3% to 4% annual increase in the incidence rate based on prepandemic temporal trends in Europe.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In this systematic review and meta-analysis, in 17 studies including 38 149 children and adolescents with newly diagnosed type 1 diabetes, 13, 23, 24, 27, 31, 32, 38, 39, 49-51, 53, 55, 58-60, 63 we found that the incidence rate of type 1 diabetes was 1.14 times higher in the first year and 1.27 times higher in the second year after the onset of the COVID-19 pandemic compared with before the pandemic. In 15 studies including a total of 4324 children and adolescents with DKA, 27,29,36,37,[40][41][42][44][45][46][47]49,50,54,65 we also found that the incidence rate of DKA at diagnosis was 1.26 times higher in the first year after the onset of the COVID-19 pandemic compared with before the pandemic. The magnitude of increase in the incidence rate of type 1 diabetes that we observed after the onset of the pandemic was greater than the expected 3% to 4% annual increase in the incidence rate based on prepandemic temporal trends in Europe.…”
Section: Discussionmentioning
confidence: 83%
“…Twenty-four studies (57.1%) reported DKA incidence at diagnosis. 3, 5, 6, 8, 9, 12, 14, 18, 19, 22, 25, 27-31, 34, 35, 37, 38, 40, 42, 48, 49 Incident cases of type 1 and type 2 diabetes were reported in 36 studies (85.7%) 12,23,24,[27][28][29][30][31][32][33][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61]63 and 9 studies (21.4%), 3,33,34,39,43,45,46,55,62 respectively. Two studies (4.8%) did not distinguish between diabetes types.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations